Soil pH and Liming Issues Affecting Bahiagrass Pasture: SS-AGR-29/AG260, 5/2007 - Silveira, Maria; Vendramini, Joao; Rechcigl, John E.; Adjei, Martin B. (EDIS, 2007)
SS-AGR-29, a 5-page illustrated fact sheet by M. Silveira, J. Vendramini, J. E. Rechcigl, and M. B. Adjei, discusses the relationships of soil acidity, nitrogen fertilizer, nutrient availability, and mole cricket-induced bahiagrass decline, and the results of a field study at Range Cattle REC in Ona, which evaluated the long term combined effect of liming and N fertilization on the performance of two bahiagrass pastures. Includes a summary and recommendations for grazing conditions in south-central Florida flatwoods. Published by the UF Department of Agronomy, May 2007.